The productions of time: a study of the human imagination - Dolzani, Michael (McGill-Queen's University Press, 2021)
"The Productions of Time argues that it is time to return to myth criticism to refine its genuine vision from its ideological limitations. Myth criticism flourished briefly in the 1960s but was eclipsed by literary theories that asserted difference and diversity and were skeptical about common, unifying patterns. But theories affirming only difference and conflict proved incapable of inspiring solidarity or guiding progressive social action. The book sketches an anatomy of the imagination as evidenced in the total body of its productions, including mythology, the arts, popular culture, and religious and political texts, thereby suggesting a symbolic language as a lingua franca enabling dialogue across ideological and individual differences. The imagination is an expanded vision of reality that does not suppress the distinction between self and other, self and world, but unites them as what William Blake called Contraries. It becomes the only possible model of a just society that does not achieve unity at the expense of differences. The Productions of Time argues that the imagination is part of the human inheritance, common to all and not just to poets and mystics."--